INSIGHTS INTO POST-MORTEM INTERVAL ESTIMATION: EXPLORING BIOLOGICAL MARKERS AND THEIR SIGNIFICANCE (Journal of Forensic Medicine & Toxicology, 2025)
Accurately estimating the post mortem interval (PMI) is crucial in forensic investigations. Biological markers within the deceased offer a promising approach for PMI estimation. [...]
Keywords: Biomarkers; Post-mortem interval; Microbiome; Omics Technologies